2016
DOI: 10.1016/j.scitotenv.2016.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Persistent organic pollutants and pregnancy complications

Abstract: We sought to investigate the relationship between maternal preconception exposures to persistent organic pollutants (POPs) and pregnancy complications, gestational diabetes (GDM) and gestational hypertension. Data from 258 (51%) women with human chorionic gonadotropin (hCG) confirmed pregnancies reaching ≥24weeks gestation, from a prospective cohort of 501 couples who discontinued contraception to attempt pregnancy, were analyzed. Preconception concentrations of 9 organochlorine pesticides (OCPs) and 10 polybr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 39 publications
2
40
0
Order By: Relevance
“…Although sperm has been traditionally considered vehicle only for the delivery of the paternal genome upon fertilization, compelling animal data demonstrate that paternal nutritional manipulation during adulthood can alter sperm epigenetic marks (Lambrot et al, 2013; Wei et al, 2014) and noncoding RNA (Sharma et al, 2016) that may affect offspring health and development. Despite the lack of mechanistic data, a growing body of human observational studies show that preconception exposures may be associated with adverse reproductive health (Bae et al, 2015; Bloom et al, 2015a; Murphy et al, 2010; Robledo et al, 2015; Smarr et al, 2016). Most notably are results indicating that male partner urinary concentrations of MMP, MnBP, and MBzP were associated with a 20% reduction in fecundity as measured by time-to-pregnancy in U.S. couples (Buck Louis et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Although sperm has been traditionally considered vehicle only for the delivery of the paternal genome upon fertilization, compelling animal data demonstrate that paternal nutritional manipulation during adulthood can alter sperm epigenetic marks (Lambrot et al, 2013; Wei et al, 2014) and noncoding RNA (Sharma et al, 2016) that may affect offspring health and development. Despite the lack of mechanistic data, a growing body of human observational studies show that preconception exposures may be associated with adverse reproductive health (Bae et al, 2015; Bloom et al, 2015a; Murphy et al, 2010; Robledo et al, 2015; Smarr et al, 2016). Most notably are results indicating that male partner urinary concentrations of MMP, MnBP, and MBzP were associated with a 20% reduction in fecundity as measured by time-to-pregnancy in U.S. couples (Buck Louis et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…One study used a nested case-control design to evaluate the PBDEs at the time of delivery and risk of preterm birth finding that higher concentrations of PBDE-47 were associated with an increased odds of preterm birth [111]. Another study evaluated pre-conception PBDEs in a prospective cohort study examining several outcomes, including GDM and gestational hypertension [112]. They found associations between PBDE-153 and an increased odds of GDM, but did not find an association with any PBDEs and gestational hypertension.…”
Section: Epidemiologic Examples Across the Life Coursementioning
confidence: 99%
“…A positive association between GDM and self-reported pesticide exposure during pregnancy has also been reported [37]. However, other studies showed no association between GDM incidence and serum organochloride pesticides [32,33] or PCB levels [33,34]. Inconsistencies between human studies can result from the inability to control certain confounding variables, such as varying POP concentrations between participants, differences in timing of POP measurements, method of diabetes diagnosis, and genetics and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, epidemiological studies investigating the association between POP exposure during pregnancy and diabetes incidence have been inconsistent. Some studies have shown a positive association between GDM and serum POP levels, including polychlorinated biphenyls (PCB) [29][30][31], polyfluoroalkyl (PFAS) [30], and polybrominated diphenyl ethers (PBDEs) [30,32]. A positive association between GDM and self-reported pesticide exposure during pregnancy has also been reported [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation